Pengaruh Customer Experience dan Kualitas Produk Terhadap Repurchase Intention pada Konsumen Shopee Food dengan Kepuasan Pelanggan Sebagai Variabel Moderating - Annisa Clara; Abdul Muslim (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study was conducted to determine how much influence Customer Experience and product quality towards Repurchase Intention on Shopee Food consumers (Case Study of Nasi Goreng Kebab Pademangan). This study uses descriptive analysis method with quantitative approach. This study took a sample of 95 respondent. Data analysis techniques in this study using Moderated Regression Analysis (MRA), with the help of SPSS ver 29. Research results demonstrate a significant impact on customer experience repurchase intent. The quality of the product does not significantly affect repurchase intent. Customer experience and product quality together have a significant influence on repurchase intention. Customer satisfaction as a moderating variable strengthens relationships customer experience of repurchase intention and influence significant. Customer satisfaction as a variable moderation does not moderate relationship between product quality and repurchase intention, and not significantly affected. Customer satisfaction as a variable moderation strengthens the relationship between customer experience and quality products with repurchase intention and significantly affected.